Entrepreneurship development management in the context of economic security - Khalatur, Svitlana; Халатур, Світлана Миколаївна; Masiuk, Yuliia; Масюк, Юлія Володимирівна; Kachula, Svitlana; Качула, Світлана Валентинівна; Brovko, Larysa; Бровко, Лариса Іванівна; Karamushka, Oleksandr; Карамушка, Олександр Миколайович; Shramko, Inna; Шрамко, Інна Іванівна (Entrepreneurship and Sustainability Center, 2021)
The article investigates theoretical and methodological approaches and practical aspects of functioning and management of socio-economic systems in modern economic conditions, develops an economic and mathematical model of economic security of business entities in conditions of risk and uncertainty, substantiates the development of Ukrainian entrepreneurship in the context of European integration challenges. The main objectives of this study are: to identify factors influencing the management of business development and the formation of economic security; study of the essence of economic security based on systematization of threats on various classification signs and definition of characteristic signs of its achievement for the realization of the further scientific developments in this direction. The problem of ensuring the development of entrepreneurship in the context of a sufficient level of economic security and the formation of favorable conditions for innovative development of enterprises today requires an adequate and timely solution and is extremely relevant. The author's definition of economic security of the enterprise is formulated, which means such a level of development of its capacities and potential that allows achieving a state of protection from internal and external economic threats in conditions of instability of the national economy. The main functional components of economic security at the level of management of a modern enterprise are highlighted. Attention is paid to the main problems of business development management in the context of economic security. The factors of development influencing economic security in the conditions of competition are formed. У статті досліджуються теоретико-методологічні підходи та практичні аспекти функціонування та управління соціально-економічними системами в сучасних економічних умовах, розробляється економіко-математична модель економічної безпеки суб’єктів господарювання в умовах ризику та невизначеності, обґрунтовується розвиток українського підприємництва в контекст викликів європейської інтеграції. Основними цілями цього дослідження є: виявлення факторів, що впливають на управління розвитком бізнесу та формування економічної безпеки; вивчення сутності економічної безпеки на основі систематизації загроз за різними класифікаційними ознаками та визначення характерних ознак її досягнення для реалізації подальших наукових розробок у цьому напрямку. Проблема забезпечення розвитку підприємництва в умовах достатнього рівня економічної безпеки та формування сприятливих умов для інноваційного розвитку підприємств сьогодні вимагає адекватного та своєчасного вирішення та є надзвичайно актуальною. Сформульовано авторське визначення економічної безпеки підприємства, що означає такий рівень розвитку його потужностей та потенціалу, що дозволяє досягти стану захисту від внутрішніх та зовнішніх економічних загроз в умовах нестабільності національної економіки. Висвітлено основні функціональні складові економічної безпеки на рівні управління сучасним підприємством. Приділено увагу основним проблемам управління розвитком бізнесу в контексті економічної безпеки. Формуються фактори розвитку, що впливають на економічну безпеку в умовах конкуренції.
Управління розвитком підприємництва в контексті економічної безпеки
Keywords: globalization; глобалізація; economy; економіка; development; розвиток; threats; загрози; security; безпека; economic security; економічна безпека; challenges; виклики; business management; управління бізнесом